Decomposition Analysis of Carbon Dioxide Emissions from the Electricity Generation Sector of India with a Policy-focused Approach and Evaluation of Scope for Raising Nationally Determined Contribution Ambitions for 2030 - Kumar, Chandan; Noh, Dongwoon (International Journal of Energy Economics and Policy, 2026)
This paper uses the Log Mean Divisia Index to decompose and analyze carbon emissions from electricity generation sector in India for the period 2014 to 2023. The overall carbon emissions grew by more than 558 Million tonnes during the period of study. The activity effect arising out of the growth in the Gross Domestic Product (GDP) has been the primary driver of growth in carbon emissions. The energy intensity of generation from thermal sources has also contributed significantly to the increase in emissions. The electricity generation intensity of the GDP is the biggest driver of emissions reduction. The falling share of thermal electricity in overall electricity generation also leads to some reduction of carbon emissions. The fuel mix effect is relatively insignificant. The emission factor remains unchanged during the period of study and has no effect on emissions. The study also analyses scenarios where different generation mixes lead to different levels of emissions reduction and uses them to analyze the scope for India to increase its NDC target of emission intensity reduction of the economy by 45% by 2030, assuming that other sectors of the GDP can achieve similar reductions. Based on the analysis in this study, it is found that India can consider enhancing its NDC target for emission intensity reduction to 55% by 2030, compared to 2005 levels, which could further influence the 2035 targets under its NDC 3.0.